(untitled) (The Pakistan Development Review, 1991)
After thirteen long years of military dictatorship, national elections on the basis of adult franchise were held in Pakistan in December 1970. The Awami League, led by Sheikh Mujibur Rahman, and the Pakistan Peoples Party, under Zulfiqar Ali Bhutto, emerged as the two majority political parties in East Pakistan and West Pakistan respectively. The political party commanding a majority in one wing of the country had almost no following in the other. This ended in a political and constitutional deadlock, since this split mandate and political exclusiveness gradually led to the parting of ways and political polarization. Power was not transferred to the majority party (that is, the Awami League) within the legally prescribed time; instead, in the wake of the political/ constitutional crisis, a civil war broke out in East Pakistan which soon led to an open war between India and Pakistan in December 1971. This ultimately resulted in the dismemberment of Pakistan, and in the creation of Bangladesh as a sovereign country. The book under review is a political study of the causes and consequences of this crisis and the war, based on a reconstruction of the real facts, historical events, political processes and developments. It candidly recapitulates the respective roles of the political elites (both of India and Pakistan), their leaders and governments, and assesses their perceptions of the real situation. It is an absorbing narrative of almost thirteen months, from 7 December, 1970, when elections were held in Pakistan, to 17 December, 1971 when the war ended after the Pakistani army’s surrender to the Indian army in Dhaka (on December 16, 1971). The authors, who are trained political scientists, give fresh interpretations of these historical events and processes and relate them to the broader regional and global issues, thus assessing the crisis in a broader perspective. This change of perspective enhances our understanding of the problems the authors discuss. Their focus on the problems under discussion is sharp, cogent, enlightening, and circumspect, whether or not the reader agrees with their conclusions. The grasp of the source material is masterly; their narration of fast-moving political events is superbly anchored in their scientific methodology and political philosophy.